The dramaturgy of the spectator : Italian theatre and the public sphere, 1600-1800 - Korneeva, Tatiana (Toronto Italian studies., 2019)
"The Dramaturgy of the Spectator: pioneers a shift in the way we think about theatre audience as both theoretical concept and historical phenomenon by examining the metomorphosis of spectators from an uncritical mass of early modern theatre-goers to an Enlightenment audience of experts and critics. This study argues for a gradual change in the self-conception of the spectatorship during the two"golden" centuries of Italian dramatic literature, outlining the dramatic strategies by which theatre called into being an adjusting audience capable of both aesthetics and political analysis. The author shows that, contrary to expectations, the public's progressive centrality to the theatre helped to create rather than hinder the playwrights's self-assertion and expression. At the same time, the discussion moves beyond spectatorship per se to consider a range of cultural assumptions and practices. These include the emergent public sphere, the power structures and social and cultural politics in Italy."--